Angiogenesis in Steno-Occlusive Vasculopathies as a Common Pathway for Intracranial Haemorrhage: A Report of Six Cases. Issue 1 (January 2014) - Van Den Berg, René; Rijssenbeek, Astrid L.; Sprengers, Marieke E.S.; Bot, Joost C.J.; Majoie, Charles B.L.M.; Roos, Yvo B.W.E.M.; Vandertop, William P.
Vasculopathies, including vasculitis of the central nervous system, can lead to stenosed, cicatrized vessels and the development of arterio-arteriolar collateral vessels. Bleeding due to these vascular changes, although rare, does occur. We describe six patients (all female, age range, 21–52 years; mean age, 42 years) with steno-occlusive lesions of intracranial vessels who presented with an acute intracranial haemorrhage. All had arterial steno-occlusive changes in conjunction with extensive leptomeningeal and arterio-arteriolar collaterals. Within the collaterals, focal dilatations could be identified, which were in close spatial relationship with the intracranial haemorrhage. Cause of bleeding was depicted on CT angiography in four out of six patients. One patient presented in childhood with acute stroke, one patient was diagnosed with Buerger's disease and one with sickle cell disease; the other three patients had no relevant history and the exact cause remained unclear. Outcome was favourable in all patients. Despite focal vascular weaknesses, no recurrent haemorrhage was seen during follow-up, supporting, at least in this small patient group, a conservative wait-and-see policy.